HISTORICAL FORENSIC PATHOLOGY - Byard, Roger (Medicinski podmladak, 2018)
Pathology is traditionally regarded as the study of injury and disease, and forensic pathology refers to those aspects of the discipline which apply to the law. Thus forensic pathologists the world over undertake much the same types of activities, performing autopsies for legal authorities, attending crime scenes with law enforcement officers, compiling reports and preparing this material for evaluation in court (1,2). Additional activities include teaching university students and trainee pathologists, as well as undertaking research. The latter activity is fascinating, as the spectrum of research in forensic pathology is vast, ranging from simple case reports detailing unusual injuries or mechanisms of death, to much more elaborate laboratory-based genetic and animal studies.